Digital Transformation in Construction Management: A Conceptual Paper - Kamil, Mohd Dhiya Hafreez; Mohd Najib Abd Rashid; Mohamed Rizal Mohamed (Emerging Advances in Integrated Technology, 2026)
This conceptual review examines the role of digital transformation in reshaping construction management practices. It aims to assess the impact of digital tools such as Building Information Modeling (BIM) and the Internet of Things (IoT), explore leadership and governance influences, and identify barriers and facilitators within the sector. Utilizing a multidisciplinary literature search across databases including IEEE Xplore and Scopus, combined with rigorous screening and quality assessment aligned with PRISMA guidelines, the review synthesizes both qualitative and quantitative findings. The analysis highlights key themes including enhanced project efficiency, sustainability outcomes, and challenges related to technology adoption and governance. The findings emphasize the critical role of integrated digital strategies and leadership in successfully driving digital transformation. This review offers foundational insights for practitioners and researchers seeking to innovate construction management processes and recommends avenues for further empirical research to deepen understanding and implementation effectiveness.